2006
DOI: 10.1111/j.1468-2354.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Fertility Rates and Female Employment Ratios Positively Correlated Across O.E.C.D. Countries?*

Abstract: We develop a quantitative theory of fertility and labor market participation decisions in order to investigate the role of labor market frictions in generating the observed positive association between fertility and employment among O.E.C.D.countries. We Þnd that unemployment induces females to postpone and space births which, in turn, reduces the total fertility rate. Moreover, differences in female labor outcomes across the U.S. and Spain can account for the low fertility rate in Spain relative to the U.S.. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 25 publications
5
64
0
3
Order By: Relevance
“…Because productivity and wage ratios are quite similar, bargaining is not affecting much the magnitude of wage ratios. 13 Earnings ratios are substantially lower than wage ratios since in our economy females with children work less hours than males (due to the time cost of children τ ). Table 10 presents wage, productivity, and earnings ratios by education categories.…”
Section: Fertility and Labor Turnover By Educationmentioning
confidence: 99%
“…Because productivity and wage ratios are quite similar, bargaining is not affecting much the magnitude of wage ratios. 13 Earnings ratios are substantially lower than wage ratios since in our economy females with children work less hours than males (due to the time cost of children τ ). Table 10 presents wage, productivity, and earnings ratios by education categories.…”
Section: Fertility and Labor Turnover By Educationmentioning
confidence: 99%
“…In Italy, using 1993 Survey of Household Income and Wealth of the Bank of Italy, it was found that higher fertility is associated to women with higher education that is currently participating in the labor force because they can afford the more quantities of children and its corresponding childcare cost (Bratti, 2003). Moreover, Da Rocha and Fuster (2006) found that fertility and employment are directly related across OECD countries and this is explained by the low probability of finding work or low employment ratio. Therefore, friction in labor market is important in establishing the relationship between fertility and female labor supply.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…La literatura científica existente a tal efecto ha demostrado que los efectos de las políticas familiares sobre la fecundidad es diversa, puesto que depende del contexto institucional y de cada hogar, aunque sí que parece ser más evidente la asociación positiva entre empleo femenino y políticas familiares, con el consiguiente efecto sobre la reproducción (Da Rocha y Fuster, 2006;Neyher, 2003).…”
Section: Introductionunclassified
“…A este respecto, partimos del hecho constatado por numerosos análisis empíricos de que, en los países del sur de Europa, y concretamente en España, contrariamente al resto de los países de la Europa de los quince, la creciente incorporación de la mujer al mercado laboral a partir de los años ochenta no ha ido pareja a un incremento en la fecundidad, sino que esta se ha mantenido a niveles reducidos (Da Rocha y Fuster, 2006;Del Boca et al, 2004;Moreno Mínguez, 2007).…”
Section: Introductionunclassified